Mechanical thrombectomy of distal occlusions in the anterior cerebral artery: recanalization rates, periprocedural complications, and clinical outcome - Pfaff, Johannes; Herweh, Christian; Pham, Mirko; Schieber, Simon; Ringleb, Peter A.; Bendszus, Martin; Möhlenbruch, Markus Alfred (American journal of neuroradiology, 2016)
BACKGROUND AND PURPOSE: Patients with acute ischemic stroke in the anterior circulation are at risk for either primary or, following mechanical thrombectomy, secondary occlusion of the anterior cerebral artery. Because previous studies had only a limited informative value, we report our data concerning the frequency and location of distal anterior cerebral artery occlusions, recanalization rates, periprocedural complications, and clinical outcome. - MATERIALS AND METHODS: We performed a retrospective analysis of prospectively collected data of patients with acute ischemic stroke undergoing mechanical thrombectomy in the anterior circulation between June 2010 and April 2015. - RESULTS: Of 368 patients included in this analysis, we identified 30 (8.1%) with either primary (n = 17, 4.6%) or secondary (n = 13, 3.5%) embolic occlusion of the distal anterior cerebral artery. The recanalization rate after placement of a stent retriever was 88%. Periprocedural complications were rare and included vasospasms (n = 3, 10%) and dissection (n = 1, 3.3%). However, 16 (53.5%) patients sustained an (at least partial) infarction of the anterior cerebral artery territory. Ninety days after the ictus, clinical outcome according to the modified Rankin Scale score was the following: 0-2, n = 11 (36.6%); 3-4, n = 9 (30%); 5-6, n = 10 (33.3%). - CONCLUSIONS: Occlusions of the distal anterior cerebral artery affect approximately 8% of patients with acute ischemic stroke in the anterior circulation receiving mechanical thrombectomy. Despite a high recanalization rate and a low complication rate, subsequent (partial) infarction in the anterior cerebral artery territory occurs in approximately half of patients. Fortunately, clinical outcome appears not to be predominately unfavorable.